There was an Old Dragon Who Swallowed a Knight - Klostermann, Penny Parker; Mantle, Ben (New York : Random House, 2015)
In this variation on the traditional cumulative rhyme, a greedy, hungry dragon eventually learns moderation.
Keywords: Folk songs, English -- Texts; Folk songs; Nonsense verses